Effects of Daylength, Temperature, Light Intensity and Applied Growth Substances on the Growth, Flowering and Tuberization of Winged Bean (Psophocarpus Tetragonolobus (L.) Dc.) - Wong, Kai Choo (1983)
The responses of vegetative growth, flowering and tuberization of a Malaysian selection (M 14/4) of winged bean (Psophocarpus tetragonolobus (L.) DC.) to daylength , aerial day/night temperature, light intensity and applied growth substance were investigated under growth cabinet, glasshouse and tropical field conditions. Plants grown at reasonably optimum day/night temperatures of 26/18'c under growth-cabinet conditions were more vigorous in vegetative growth with increase in daylength. However, with higher temperature regimes, this daylength effect on vegetative growth was reversed. Increase in daylength generally led to higher dry matter in the stem and less to the leaf and root system. It also resulted in higher specific leaf area and less total chlorophyll contentin the leaves. There was no evidence from the present study of a thermoperiodic response. Reducing the intensity of the natural daylight led to an increase in leaf area ratio and consequently a higher relative growth rate up to a maximum of about 45% of full natural light in tensity. Increase in nodulation was also obtained with reduction in natural light intensity. Extension growth was gene rally increased by application of GA and decreased by CCC and phosphon without affecting dry matter redistribution between the various plant organs. Short days were necessary for both flower initiation and development. A minimum number of leave s mus t have been formed on the main axis before the plant can be induced to initiate flowers.